How to give a speech - Ryan, Margaret (New York : F. Watts, 1994)
Provides a complete, easy-to-follow course in speechmaking, from how to choose a topic and research it, to how to write and effectively deliver the speech. Includes tips on assessing the audience, writing outlines and drafts, practicing the delivery, using humor and visuals, developing a style, and other techniques.
Includes bibliographical references (p. 136-138) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Public speaking -- Juvenile literature; Public speaking; Public speaking